Delayed childhood neuropsychomotor development: main prenatal, intrinsic and extrinsic causes (Research, Society and Development, 2023)
Child development is a process that goes from conception, involving several aspects, from physical growth, through the child's neurological, behavioral, cognitive, social and affective maturation. Its product is to make the child competent to respond to their needs and those of their environment, considering their life context. Extrinsic factors such as adequate nutrition, biopsychosocial stimuli and physical activity, as well as intrinsic factors (genetics, neuroendocrine system), will have profound and marked influences on both the growth and development of a child. Various diseases, whether of a deficient nature (e.g.: malnutrition, physical, psychological, sexual violence, neglect), genetic (e.g.: chromosomal disorders, various mutations), neoplastic, infectious, inflammatory, can negatively influence growth and/or development.